Bimetal catalyst with core-shell structure as well as preparation method and application of bimetallic catalyst

By using a core-shell bimetallic catalyst, with a core consisting of bimetallic nanoparticles supported by molecular sieves and a shell of biochar, the problems of easy sintering and carbon deposition deactivation of nickel-based catalysts under high temperature and high pressure are solved, achieving efficient biodiesel production and improving the stability and activity of the catalyst.

CN121467091APending Publication Date: 2026-02-06GUANGZHOU MARITIME INST
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202610024006.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-09
Publication Date
2026-02-06

AI Technical Summary

Technical Problem

Existing nickel-based catalysts are prone to sintering and loss in high-temperature and high-pressure reaction environments, leading to reduced activity and carbon buildup and deactivation, which affects the production efficiency and quality of second-generation biodiesel.

Method used

The bimetallic catalyst with a core-shell structure has a core of bimetallic nanoparticles supported by molecular sieves and a shell of biochar. The electronic structure of Ni is modulated by the second metal M to enhance the deoxygenation capacity, and the biochar shell prevents the sintering and loss of Ni-based nanoparticles.

Benefits of technology

It significantly improves the stability and service life of the catalyst, achieves synergistic effects of hydrogenation, deoxygenation, cracking and isomerization, and produces high-grade biodiesel with an alkane selectivity of over 90%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121467091A_ABST
    Figure CN121467091A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalysts, and particularly discloses a bimetallic catalyst of a core-shell structure and a preparation method and application thereof.The bimetallic catalyst of the core-shell structure comprises an inner core and an outer shell, the inner core comprises a molecular sieve serving as a carrier and bimetallic nano-particles loaded on the molecular sieve, and the outer shell comprises the molecular sieve and bimetallic nano-particles loaded on the molecular sieve; the shell is a biochar shell coating the inner core, the bimetallic nanoparticles are composed of nano-sized Ni and a second metal M, and the second metal M is one of Mo, W, Co or Ti. The bimetallic catalyst with the core-shell structure provided by the invention has the advantages of stable structure, low cost, high activity and high selectivity, and the preparation method is simple.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of catalysts, and particularly relates to a bimetallic catalyst with a core-shell structure and a preparation method and application thereof. BACKGROUND

[0002] Second-generation biodiesel, also known as green diesel, is an alkane fuel produced through the hydrogenation deoxygenation (HDO) process of animal and vegetable oils. Its main components are similar to petroleum-based diesel, but it has significant advantages in performance and environmental protection. Specifically, second-generation biodiesel has a higher cetane number, which allows it to burn more quickly and completely during combustion, effectively improving engine power performance and fuel economy. At the same time, its better environmental protection is reflected in lower pollutant emissions during combustion, which helps to reduce the negative impact on the environment and meets the urgent needs of society for clean energy. With the continuous growth of global energy demand and the increasing emphasis on environmental protection, second-generation biodiesel, as a highly potential renewable clean energy, has a growing market demand, and developing efficient, environmentally friendly, and economical preparation processes has become the focus of the industry.

[0003] In the preparation process of second-generation biodiesel, the hydrogenation deoxygenation catalyst plays a key role. Currently, nickel-based catalysts have shown great application potential in the field of second-generation biodiesel preparation due to their excellent hydrogenation activity and relatively low cost. However, in the actual high-temperature and high-pressure reaction environment, nickel-based catalysts face serious stability and carbon deposition problems: (1) Easy sintering and loss: Under high-temperature and high-pressure conditions, nickel particles in nickel-based catalysts are prone to sintering, leading to an increase in particle size, a decrease in specific surface area, and a reduction in active site number, thereby significantly reducing the hydrogenation activity of the catalyst. At the same time, nickel particles may also be lost from the support, further weakening the performance of the catalyst and affecting the continuous operation of the reaction and the quality of the product.

[0004] (2) Carbon deposition inactivation: The carbon produced during the reaction will cover the surface of the nickel-based catalyst, hindering the contact between the reactants and the active centers, reducing the activity of the catalyst, and even completely deactivating the catalyst, which seriously affects the preparation efficiency and product quality of second-generation biodiesel.

[0005] In addition, the current preparation method of nickel-based catalysts usually uses an impregnation method to directly load nickel on molecular sieves, but the nickel particles prepared by this method have weak interaction with the support and are exposed on the surface, which are prone to sintering or loss during the reaction, affecting the performance of the nickel-based catalyst.

[0006] Therefore, it is urgent to develop a catalyst that can solve the above problems. SUMMARY

[0007] The present application aims at the problems of the prior art, and provides a bimetallic catalyst with core-shell structure, a preparation method and application.

[0008] To solve the above technical problems, the present application provides a bimetallic catalyst with core-shell structure, comprising an inner core and an outer shell, wherein the inner core comprises a molecular sieve as a carrier and bimetallic nanoparticles loaded on the molecular sieve, and the outer shell is a biochar shell coated on the inner core, and the bimetallic nanoparticles are composed of Ni and a second metal M in nanometer size, and the second metal M is one of Mo, W, Co or Ti.

[0009] The bimetallic catalyst with core-shell structure provided by the present application modulates the electronic structure of Ni by introducing the second metal M, and enhances the deoxidation capacity. After being combined with the molecular sieve, the hydrogenation, deoxidation, cracking and isomerization are synergized, the bimetallic nanoparticles loaded on the molecular sieve are coated by the biochar shell, which provides excellent hydrogenation activity for the catalyst, in addition, the biochar coating layer effectively prevents the sintering and loss of Ni-based nanoparticles in high-temperature reaction, and inhibits the generation of carbon deposition, thereby significantly improving the stability and service life of the catalyst.

[0010] The principle of modulating the electronic structure of Ni by introducing the second metal M is as follows: when the second metal M is Mo / W, the Ni 3d orbital overlaps with the Mo / W 4d orbital, so that the orbitals are hybridized, and the electronegativity of Mo / W (Mo: 2.16 V, W: 2.36 V) is slightly higher than the electronegativity of Ni (1.91 V), so that the electrons of Ni are transferred to Mo / W, the electron cloud density on the surface of Ni is reduced, and the adsorption energy of oxygen atoms is significantly enhanced, thereby enhancing the deoxidation capacity.

[0011] When the second metal M is Co, Ni-Co forms an alloy phase (i.e., a Ni-Co solid solution), the electronegativity of Co (1.88 V) is close to the electronegativity of Ni (1.91 V), and the electrons are slightly biased in both directions (slightly Ni ↔ Co); and the d orbital overlap degree in the Ni-Co alloy is high, and the d band filling degree of Ni is improved, so that the electron cloud density on the surface of Ni is uniformly distributed, and the uniform electron cloud distribution enables the Ni surface to simultaneously and efficiently activate the C-O bond and H2 molecules, thereby promoting the deoxidation and hydrogenation reaction.

[0012] When the second metal M is Ti, the electronegativity of Ti (1.54 V) is much lower than that of Ni (1.91 V), and Ti transfers electrons to Ni, so that the electron cloud density of the surface of Ni is significantly increased; however, the 3d orbit of Ti is hybridized with the 3d orbit of Ni, which shrinks the d-band width of Ni and enhances the electron localization, and after the d-band width is shrunk, the d-orbital energy of Ni is increased, and the interaction between Ni and the oxygen-containing intermediate (such as O, OH, OOH, etc.) is enhanced, which makes the oxygen-containing intermediate more easily adsorbed and activated on the surface of Ni, thereby promoting the breaking of the C-O bond.

[0013] Preferably, the molar ratio of Ni to the second metal M in the bimetallic nanoparticles is (1-5):1.

[0014] In the present application, within this molar ratio range, the Ni of the main hydrogenation active center and the second metal M of the synergistic regulation center can form a stable “active-regulation” synergistic system, and the electronic / structural effect of M regulates the oil hydrogenation reaction activity and selectivity of Ni. If M is too much, an independent inert phase (such as the oxide of M, elemental particles) is easily formed, which cannot form an effective alloy with Ni. If Ni is too much, the particles will become large and form agglomeration, which affects the reaction activity of the catalyst.

[0015] Preferably, the size of the bimetallic nanoparticles is 5-10 nm.

[0016] In the present application, the size of the bimetallic nanoparticles is 5-10 nm measured by TEM projection electron microscope, and when the size is 5-10 nm, the size is moderate, which avoids agglomeration caused by too high surface energy when the size is <5 nm, and the active sites are wrapped after agglomeration, so that the reaction rate is reduced, and also avoids the sharp reduction of specific surface area and the reduction of active sites when the size is >10 nm, so that the catalytic efficiency is reduced.

[0017] Preferably, the molecular sieve is one of HZSM-5, HZSM-22, or SAPO-11.

[0018] In the present application, HZSM-5, HZSM-22, or SAPO-11 is selected as the carrier because these three molecular sieves are all one-dimensional ten-membered ring structures, the acidity can be adjusted, and the three molecular sieves are not easy to collapse under high temperature and high pressure, and have the ability to resist carbon deposition and metal poisoning.

[0019] The second aspect of the present application provides a preparation method of the bimetallic catalyst with the above-mentioned core-shell structure, which comprises the following steps: (1) adding a molecular sieve, a nickel salt and a second metal M salt into an organic solvent to form a uniform suspension A by stirring; (2) adding a biomass raw material into deionized water to form a uniform suspension B by stirring; (3) Mix suspension A and suspension B, and stir under heating conditions of 80-100℃ until the liquid is completely evaporated to obtain a solid precursor mixture; (4) The solid precursor mixture obtained in step (3) is heated under an inert atmosphere to pyrolyze and carbonize, so that the nickel salt and the second metal salt are reduced. At the same time, the biomass raw material is carbonized to form a biochar shell coated on the bimetallic nanoparticles, and the catalyst primary product is obtained. After grinding, the catalyst is obtained.

[0020] The method for preparing core-shell bimetallic catalysts provided by this invention uses biomass raw materials as carbon sources, which is low-cost and renewable. The preparation process is simple, requires no complicated post-processing, and is easy to scale up.

[0021] Preferably, in step (1), the nickel salt is selected from one of nitrate, sulfate, acetate or hydrochloride; the second metal M salt is selected from one of ammonium M salt, nitrate, sulfate, acetate or hydrochloride.

[0022] Preferably, in step (1), the organic solvent is one of propanol, ethanol or tert-butanol.

[0023] In this invention, propanol, ethanol, or tert-butanol all contain a hydroxyl group (-OH), which can react with Ni. 2+ This process forms a stable complex with moderate activity, avoiding both excessively strong complexation that would hinder Ni reduction to the active component and excessively weak complexation that would cause Ni ion aggregation, thus ensuring catalyst dispersibility. Furthermore, the boiling points of these three alcohols are between 75-100℃, allowing excess non-complexing solvent to easily volatilize.

[0024] Preferably, the molar ratio of the total metal ions of the biomass raw material to the nickel salt and the second metal M salt is (0.5-2):1, and the biomass raw material is one of sucrose, D-glucose, D-sorbitol citric acid, or hydrogen peroxide-pretreated cellulose. Hydrogen peroxide-pretreated cellulose is preferred.

[0025] In the invention, the biomass raw material provides a bio-carbon shell after pyrolysis. If the molar ratio is too low (<0.5:1), the carbon source is insufficient and cannot completely coat the metal particles, which easily leads to particle agglomeration and oxidation. If the molar ratio is too high (>2:1), the carbon layer is too thick, which hinders the contact between the reactant (oil) and the active site (Ni / M alloy) and increases the cost of catalyst preparation.

[0026] Preferably, the mass ratio of the biomass raw material to deionized water is (0.01-0.07):1.

[0027] It should be noted that in step (1), the organic solvent is added according to the ratio of molecular sieve, wherein the mass ratio of molecular sieve to organic solvent is 1g:30ml.

[0028] Preferably, the heating rate of the pyrolysis carbonization process is 5-15℃ / min, the temperature is raised to 500-800℃, and then calcined at a constant temperature of 500-800℃ for 1-4 hours.

[0029] More preferably, the heating rate of the pyrolysis carbonization process is 10℃ / min, the temperature is raised to 600℃-800℃, and then calcined at a constant temperature of 600℃-800℃ for 2 hours.

[0030] In this invention, within the temperature range of 600-800℃, biomass raw materials can be completely pyrolyzed and carbonized (i.e., volatile matter is removed, and graphitized carbon is formed). The biomass carbon shell has moderate porosity, good electrical conductivity, and high mechanical strength, effectively encapsulating metal particles. Below 600℃, carbonization is incomplete, the carbon shell contains a large number of impurities, and the pore structure is poor. Above 800℃, the carbon shell is excessively graphitized, the pores collapse, mass transfer resistance increases, and metal particles are prone to sintering and growth. Simultaneously, Ni can be achieved at 600-800℃. 2+ / M n+ Highly efficient restoration.

[0031] A third aspect of the present invention also provides the application of the above-described core-shell structured bimetallic catalyst in the catalytic hydrodeoxygenation reaction of waste oils.

[0032] Preferably, the specific steps of the catalytic hydrodeoxygenation reaction of waste oil are as follows: a core-shell bimetallic catalyst and waste oil raw material are added to a high-pressure reactor and reacted for 2-5 hours at a hydrogen pressure of 2-10 MPa and a reaction temperature of 250-450°C, wherein the amount of catalyst used is 5%-10% of the mass of the waste oil raw material.

[0033] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The core-shell bimetallic catalyst provided by this invention modulates the electronic structure of Ni by introducing a second metal M. The introduction of the second metal M changes the d-band center and electron cloud density of Ni, which enhances the dissociation and adsorption of H2 (H2→2H*, hydrogenation rate control step) and optimizes the adsorption strength of C=C double bonds in oils, thus enhancing its deoxygenation ability. After being combined with molecular sieve, it achieves synergistic effects of hydrogenation, deoxygenation, cracking, and isomerization. The bimetallic nanoparticles loaded on the molecular sieve are coated with a biochar shell. The biochar shell inhibits the aggregation and loss of bimetallic nanoparticles, maintains the stability of active sites, and provides excellent hydrogenation activity for the catalyst. In addition, the biochar coating layer effectively prevents the sintering and loss of Ni-based nanoparticles in high-temperature reactions, while inhibiting the formation of carbon deposits, which significantly improves the stability and service life of the catalyst.

[0034] (2) The core-shell bimetallic catalyst provided by the present invention is applied to the catalytic hydrodeoxygenation reaction of waste oil, realizing the synergy of hydrogenation, deoxygenation, cracking and isomerization, directly generating high-grade biodiesel, with alkane selectivity of over 90%. Attached Figure Description

[0035] Figure 1 The graph shows the cyclic reaction performance of the NiMo@C / HZSM-5 catalyst for deoxygenation and hydrogenation of waste oil prepared in Example 1.

[0036] Figure 2 The image shows a transmission electron microscope (TEM) image of NiMo@C / HZSM-5 prepared in Example 1. Detailed Implementation

[0037] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the specific embodiments will be explained below in conjunction with the accompanying drawings.

[0038] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.

[0039] It should be noted that in the following embodiments, the mass loading of the bimetallic nanoparticles is within 10% according to theoretical calculations, and the encapsulation amount of the biological shell is 6-20% according to theoretical calculations. Specific measurement values ​​are given in each embodiment and comparative example below.

[0040] All raw materials used in the following examples are commercially available. In the specific examples below, the molecular sieve used is HZSM-5 molecular sieve, and the biomass feedstock is cellulose pretreated with hydrogen peroxide.

[0041] Example 1

[0042] This embodiment provides a method for preparing a core-shell bimetallic catalyst, comprising the following steps: 1.0 g HZSM-5 molecular sieve, 0.436 g nickel nitrate hexahydrate (Ni(NO3)2·6H2O) and 0.088 g ammonium molybdate ((NH4)6Mo7O) were added. 24 ·4H2O) was added to 30 mL of ethanol and stirred to form a homogeneous suspension A. The molar ratio of nickel to molybdenum was 3:1 (i.e., n: 4H2O). Ni =0.0015mol, n Mo =0.0005 mol).

[0043] (2) Add 0.324 g of cellulose pretreated with hydrogen peroxide to 10 mL of deionized water and stir to form a uniform suspension B. The pretreatment method is as follows: soak the cellulose in a 5% hydrogen peroxide solution for 1 hour, then wash and dry. The molar ratio of the pretreated cellulose to the total metal ions is 1:1 (n... metal total =0.002mol).

[0044] (3) Mix suspension A and suspension B, and heat at 80°C and stir continuously until the liquid is completely evaporated to obtain a solid precursor mixture.

[0045] (4) The solid precursor mixture was heated to 600°C under nitrogen at a heating rate of 10°C / min and calcined at this temperature for 2 hours to reduce nickel nitrate and ammonium molybdate to obtain bimetallic nanoparticles. At the same time, cellulose was carbonized to form a biochar shell covering the bimetallic nanoparticles to obtain the catalyst primary product. The catalyst primary product was ground to obtain a black powder catalyst, denoted as NiMo@C / HZSM-5 (wherein, the mass loading of nickel was 6.87% and the mass loading of molybdenum was 3.21% as tested by ICP-OES; and the biochar coating amount was 10.23% as tested by thermogravimetric analysis).

[0046] Transmission electron microscopy (TEM) was performed on the NiMo@C / HZSM-5 prepared in Example 1, and the results were obtained. Figure 2 ,from Figure 2 It can be seen that the size of the NiMo@C / HZSM-5 bimetallic nanoparticles prepared in Example 1 is 6.9 nm.

[0047] Example 2

[0048] This embodiment provides a method for preparing a core-shell bimetallic catalyst, comprising the following steps: (1) 1.0g HZSM-5 molecular sieve, 0.388g nickel nitrate (Ni(NO3)2·6H2O) and 0.174g ammonium tungstate ((NH4) 10 W12 O 41 ·5H₂O) was added to 30 mL of tert-butanol and stirred to form a homogeneous suspension A. The molar ratio of nickel to tungsten was 2:1 (i.e., n: 5H₂O). Ni =0.001333 mol, n W =0.000667mol).

[0049] (2) Add 0.486 g of cellulose pretreated with hydrogen peroxide (pretreatment method as in Example 1) to 10 mL of deionized water and stir to form a uniform suspension B. The molar ratio of pretreated cellulose to total metal ions is 1.5:1 (n... metal total =0.002mol).

[0050] (3) Mix suspension A and suspension B, and heat at 80°C and stir continuously until the liquid is completely evaporated to obtain a solid precursor mixture.

[0051] (4) The solid precursor mixture was heated to 800°C at a heating rate of 10°C / min under a nitrogen atmosphere and calcined at this temperature for 2 hours to reduce nickel nitrate and ammonium tungstate to obtain bimetallic nanoparticles. At the same time, cellulose was carbonized to form a biochar shell covering the bimetallic nanoparticles to obtain the catalyst primary product. The catalyst primary product was ground to obtain a black powder catalyst, denoted as NiW@C / HZSM-5 (wherein, the mass loading of nickel was 5.24% and the mass loading of molybdenum was 7.93% as tested by ICP-OES; and the biochar coating amount was 14.69% as tested by thermogravimetric analysis).

[0052] Example 3

[0053] This embodiment provides a method for preparing a core-shell bimetallic catalyst, comprising the following steps: (1) Add 1.0 g of HZSM-5 molecular sieve, 0.465 g of nickel nitrate (Ni(NO3)2·6H2O) and 0.116 g of cobalt nitrate (Co(NO3)2·6H2O) to 30 mL of ethanol and stir to form a homogeneous suspension A. The molar ratio of nickel to cobalt is 4:1 (i.e., n...). Ni =0.0016mol, n Co =0.0004mol).

[0054] (2) 0.162 g of cellulose pretreated with hydrogen peroxide (pretreatment method as in Example 1) was added to 10 mL of deionized water to form suspension B. The molar ratio of pretreated cellulose to total metal ions was 0.5:1 (n... metal total =0.002mol).

[0055] (3) Mix suspension A and suspension B and stir continuously at 80°C until the liquid completely evaporates to obtain a solid precursor mixture.

[0056] (4) The solid precursor mixture was heated to 600°C at a heating rate of 10°C / min under a nitrogen atmosphere and calcined at this temperature for 2 hours to reduce nickel nitrate and cobalt nitrate to obtain bimetallic nanoparticles. At the same time, cellulose was carbonized to form a biochar shell covering the bimetallic nanoparticles to obtain the catalyst primary product. The catalyst primary product was ground to obtain a black powder catalyst, named NiCo@C / HZSM-5 (wherein, the mass loading of nickel was 7.17% and the mass loading of molybdenum was 1.78% as tested by ICP-OES; and the biochar coating amount was 6.01% as tested by thermogravimetric analysis).

[0057] Example 4

[0058] This embodiment provides a method for preparing a core-shell bimetallic catalyst, comprising the following steps: (1) Add 1.0 g HZSM-5 molecular sieve, 0.291 g nickel nitrate (Ni(NO3)2·6H2O) and 0.178 g titanium oxysulfate (TiOSO4·H2O) to 30 mL of ethanol and stir to form a uniform suspension A. The molar ratio of nickel to titanium is 1:1 (n... Ni =0.001mol, n Ti =0.001mol).

[0059] (2) Add 0.648g of cellulose pretreated with hydrogen peroxide (pretreatment method is the same as in Example 1) to 10mL of deionized water and stir to form a uniform suspension B. The molar ratio of the pretreated cellulose to the total metal ions is 2:1 (n metal total =0.002mol).

[0060] (3) Mix solution A and solution B and stir continuously at 80°C until the liquid completely evaporates to obtain a solid precursor mixture.

[0061] (4) The solid precursor mixture was heated to 600°C at a rate of 10°C / min under a nitrogen atmosphere and calcined at this temperature for 2 hours to reduce nickel nitrate and titanium oxysulfate to obtain bimetallic nanoparticles. At the same time, cellulose was carbonized to form a biochar shell covering the bimetallic nanoparticles to obtain the catalyst primary product. The catalyst primary product was ground to obtain a black powder catalyst, named NiTi@C / HZSM-5 (wherein, the mass loading of nickel was 4.18% and the mass loading of molybdenum was 3.25% as tested by ICP-OES; and the biochar coating amount was 19.72% as tested by thermogravimetric analysis).

[0062] Example 5

[0063] This embodiment provides a method for preparing a core-shell bimetallic catalyst, comprising the following steps: (1) 1.0 g HZSM-5 molecular sieve, 0.415 g nickel acetate (Ni(CH3COO)2·4H2O) and 0.083 g cobalt acetate (Co(CH3COO)2·4H2O) were added to 30 mL tert-butanol and stirred to form a homogeneous suspension A. The molar ratio of nickel to cobalt was 5:1 (n... Ni =0.001667 mol, n Co =0.000333mol).

[0064] (2) Add 0.389 g of cellulose pretreated with hydrogen peroxide (pretreatment method as in Example 1) to 10 mL of deionized water and stir to form a uniform suspension B. The molar ratio of pretreated cellulose to total metal ions is 1.2:1 (n... metal total =0.002mol).

[0065] (3) Mix suspension A and suspension B and stir continuously at 80 °C until the liquid completely evaporates to obtain a solid precursor mixture.

[0066] (4) The solid precursor mixture was heated to 600°C under nitrogen at a heating rate of 10°C / min and calcined at this temperature for 2 hours to reduce nickel acetate and cobalt acetate to obtain bimetallic nanoparticles. At the same time, cellulose was carbonized to form a biochar shell covering the bimetallic nanoparticles to obtain the catalyst primary product. The catalyst primary product was ground to obtain a black powder catalyst, named NiCo@C / HZSM-5 (wherein, the mass loading of nickel was 7.05% and the mass loading of molybdenum was 1.41% as tested by ICP-OES; and the biochar coating amount was 12.63% as tested by thermogravimetric analysis).

[0067] Comparative Example 1: Preparation of Ni / HZSM-5 catalyst by conventional impregnation method Using the equal-volume impregnation method, 0.347 g of nickel nitrate hexahydrate was dissolved in deionized water and then added dropwise to 1.0 g of HZSM-5 molecular sieve. After impregnation for 12 hours, the solution was dried at 105 °C and finally reduced at 600 °C for 2 hours in a 5% hydrogen / nitrogen mixed atmosphere to obtain a 7% Ni / HZSM-5 catalyst.

[0068] Comparative Example 2 This comparative example provides a method for preparing a core-shell structured metal catalyst, comprising the following steps: (1) Add 1.0g HZSM-5 molecular sieve and 0.582g nickel nitrate (Ni(NO3)2·6H2O) to 30mL ethanol and stir to form a uniform suspension A.

[0069] (2) Add 0.324 g of cellulose pretreated with hydrogen peroxide (pretreatment method: soak the cellulose in 5% hydrogen peroxide solution for 1 hour, then wash and dry) to 10 mL of deionized water and stir to form a uniform suspension B. The molar ratio of the pretreated cellulose to nickel is 1:1 (n... Ni =0.002mol).

[0070] (3) Mix suspension A and suspension B, and stir continuously at 80°C until the liquid completely evaporates to obtain a solid precursor mixture.

[0071] (4) The solid precursor mixture was heated to 600°C at a heating rate of 10°C / min under a nitrogen atmosphere and calcined at this temperature for 2 hours to obtain the catalyst primary product. After grinding, the catalyst primary product was obtained as a black powder catalyst, denoted as Ni@C / HZSM-5 (wherein, the mass loading of nickel was 5.95% as determined by ICP-OES and the biochar encapsulation amount was 6.53% as determined by thermogravimetric analysis).

[0072] Comparative Example 3 This comparative example provides a method for preparing a bimetallic catalyst, comprising the following steps: (1) 1.0g HZSM-5 molecular sieve, 0.436g nickel nitrate (Ni(NO3)2·6H2O) and 0.088g ammonium molybdate ((NH4)6Mo7O) 24 ·4H2O) was added to 30 mL of ethanol and stirred to form a homogeneous suspension A. The molar ratio of nickel to molybdenum was 3:1 (n...). Ni =0.0015mol, n Mo =0.0005mol).

[0073] (2) The suspension A was heated at 80°C and stirred continuously until the liquid was completely evaporated to obtain a mixture of solid precursors.

[0074] (3) The solid precursor mixture was heated to 600°C at a heating rate of 10°C / min under a nitrogen atmosphere and calcined at this temperature for 2 hours to reduce nickel nitrate and ammonium molybdate to obtain the catalyst primary product. The catalyst primary product was ground to obtain a black powder catalyst, denoted as NiMo / HZSM-5 (wherein, the mass loading of nickel was 5.53% and the mass loading of molybdenum was 3.01% as determined by ICP-OES).

[0075] Comparative Example 4 This comparative example provides a method for preparing a core-shell bimetallic catalyst, comprising the following steps: 1.0 g HZSM-5 molecular sieve, 0.436 g nickel nitrate (Ni(NO3)2·6H2O) and 0.088 g ammonium molybdate ((NH4)6Mo7O) were added. 24 ·4H2O) was added to 30 mL of ethanol and stirred to form a homogeneous suspension A. The molar ratio of nickel to molybdenum was 3:1 (i.e., n: 4H2O). Ni =0.0015mol, n Mo =0.0005mol).

[0076] (2) Add 0.00648g of cellulose pretreated with hydrogen peroxide to 10mL of deionized water and stir to form a uniform suspension B. The pretreatment method is as follows: soak the cellulose in 5% hydrogen peroxide solution for 1 hour, then wash and dry. The molar ratio of the pretreated cellulose to the total metal ions is 1:50.

[0077] (3) Mix suspension A and suspension B, and heat at 80°C and stir continuously until the liquid is completely evaporated to obtain a solid precursor mixture.

[0078] (4) The solid precursor mixture was heated to 600 °C at a heating rate of 10 °C / min under nitrogen, and calcined at this temperature for 2 hours to reduce nickel nitrate and ammonium molybdate to obtain bimetallic nanoparticles. At the same time, cellulose was carbonized to form a biochar shell covering the bimetallic nanoparticles to obtain the catalyst primary product. The catalyst primary product was ground to obtain a black powder catalyst, named NiMo@C / HZSM-5 (wherein, the mass loading of nickel was 5.46% and the mass loading of molybdenum was 3.03% as tested by ICP-OES; and the biochar coating amount was 0.17% as tested by thermogravimetric analysis).

[0079] Comparative Example 5 This comparative example provides a method for preparing a core-shell structured metal catalyst, comprising the following steps: 1.0 g HZSM-5 molecular sieve, 0.436 g nickel nitrate (Ni(NO3)2·6H2O) and 0.088 g ammonium molybdate ((NH4)6Mo7O) were added. 24 ·4H2O) was added to 30 mL of ethanol and stirred to form a homogeneous suspension A. The molar ratio of nickel to molybdenum was 3:1 (i.e., n: 4H2O). Ni =0.0015mol, n Mo =0.0005mol).

[0080] 0.972 g of cellulose pretreated with hydrogen peroxide was added to 10 mL of deionized water and stirred to form a homogeneous suspension B. The pretreatment method involved soaking the cellulose in a 5% hydrogen peroxide solution for 1 hour, followed by washing and drying. The molar ratio of the pretreated cellulose to the total metal ions was 3:1.

[0081] Suspension A and suspension B are mixed and heated at 80°C with continuous stirring until the liquid is completely evaporated, resulting in a solid precursor mixture.

[0082] The solid precursor mixture was heated to 600°C under nitrogen at a heating rate of 10°C / min and calcined at this temperature for 2 hours to reduce nickel nitrate and ammonium molybdate, yielding bimetallic nanoparticles. Simultaneously, cellulose was carbonized to form a biochar shell coating the bimetallic nanoparticles, yielding the catalyst primary product. The catalyst primary product was ground to obtain a black powdered catalyst, denoted as NiMo@C / HZSM-5 (wherein, the mass loading of nickel was 3.15% and the mass loading of molybdenum was 1.74% as determined by ICP-OES; and the biochar coating amount was 14.69% as determined by thermogravimetric analysis).

[0083] Application Example 1 Waste oil (specific components are shown in Table 1) and the catalyst prepared in Example 1 were added to a high-pressure reactor at 330°C and 4MPa H2 pressure, and hydrogenated for 4 hours. The amount of catalyst used was 5% of the mass of the waste oil raw material.

[0084] Application Example 2-5 Referring to Application Example 1, Application Examples 2-5 respectively replaced the catalyst prepared in Example 1 with the catalyst prepared in Examples 2-5, while keeping the other conditions unchanged.

[0085] Compare and contrast examples 1-5 Referring to Application Example 1, in Comparative Application Examples 1-5, the catalyst prepared in Example 1 was replaced with the catalyst prepared in Comparative Examples 1-5, while the other conditions remained unchanged.

[0086] Test Example 1 Liquid products were analyzed using Agilent gas chromatography and gas chromatography-mass spectrometry (GC-MS), and the selectivity of C8-C18 alkane products was calculated according to the specific product calculation formula, where: C8-C18 alkane product selectivity = (amount of C8-C18 alkane / total amount of liquid product) × 100%; C8-C18 n-alkane selectivity = (amount of n-alkane in C8-C18 products / total amount of liquid products) × 100%; Selectivity for C8-C18 isoalkanes = (Amount of isoalkanes in C8-C18 products / Total amount of liquid products) × 100%; The selectivity of aromatics = (amount of aromatics in the product / total amount of liquid product) × 100%. The calculation results are recorded in Table 2 below.

[0087] Table 1. Composition and acid value of waste oils

[0088] Table 2. Effects of different catalysts on the selectivity of catalytic hydrogenation products of waste oils

[0089] As can be seen from the data in Table 2, when the catalysts prepared in Examples 1-5 of the present invention catalyze waste oils, the catalysts show high selectivity for C8-C18 n-alkanes, aromatics and C8-C18 isoalkanes, with the C8-C18 alkane selectivity all above 90%.

[0090] Data from Comparative Example 1 and Application Example show that the Ni / HZSM-5 catalyst prepared by the traditional impregnation method exhibits zero selectivity for isoparaffins and only 77.6% selectivity for C8-C18 alkanes when catalyzing waste oils. This indicates that the nickel particles prepared by the traditional impregnation method have weak interaction with the support and are exposed on the surface, making them prone to sintering or loss during the reaction, thus reducing the selectivity of the catalyst.

[0091] The data from Comparative Example 2 and Application Example 1 show that when the catalyst contains only nickel and no second metal, the selectivity for isoalkanes is much lower, and the selectivity for C8-C18 alkanes is only 83.8%. This indicates that when the second metal M is present, Ni cannot be controlled by the electronic / structural effect of M, and the activity and selectivity of the prepared catalyst for the hydrogenation reaction of oils and fats are both low.

[0092] The data from Comparative Example 3 and Application Example 1 show that when preparing the catalyst, without adding hydrogen peroxide pretreated cellulose to form a biochar shell, the selectivity for isoparaffins is 22.9%, and the selectivity for C8-C18 alkanes is 88.3%, which is much lower than the selectivity of NiMo@C / HZSM-5 prepared in Example 1. This indicates that without a biochar shell to coat the bimetallic nanoparticles on the supported molecular sieve, the bimetallic nanoparticles in the prepared catalyst are prone to agglomeration and loss, resulting in a decrease in the hydrogenation activity of the catalyst.

[0093] The data from Comparative Examples 4, 5 and 1 show that both low and high molar ratios of pretreated cellulose to metal ions affect the selectivity of the catalyst. When the molar ratio is too low, the carbon source is insufficient, and the biochar shell cannot completely coat the metal particles, which easily leads to the agglomeration and oxidation of bimetallic particles, weakening the performance of the catalyst. When the molar ratio is too high, the carbon layer is too thick, which hinders the contact between the reactant oil and the active site (Ni / M alloy), reducing the activity of the catalyst and its selectivity.

[0094] Test Example 2 At 330°C and 4MPaH2 pressure, waste oil (specific components are shown in Table 1) and the catalyst prepared in Example 1 were put into a high-pressure reactor and hydrogenated for 4 hours, wherein the catalyst was 5% of the mass of the oil raw material.

[0095] After the reaction was completed, the catalyst prepared in Example 1 was recovered. The same mass of waste oil was added, and under the same reaction conditions, a hydrogenation reaction was carried out for 4 hours. This process was repeated three more times with the same mass of waste oil added. The conversion rate was calculated for each of the five reactions, and the results are as follows: Figure 1 As shown.

[0096] from Figure 1 It can be seen that the conversion rate of NiMo@C / HZSM-5 prepared in Example 1 for the first catalytic hydrogenation of waste oil was 96.1%, and the conversion rate for the fifth catalytic hydrogenation of waste oil was still 71.2%, indicating that NiMo@C / HZSM-5 prepared in Example 1 has strong reactivity and stability.

[0097] Based on the disclosure and teachings of the foregoing specification, those skilled in the art can make changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments disclosed and described above, and some modifications and changes to the invention should also fall within the protection scope of the claims of the present invention. Furthermore, although some specific terms are used in this specification, these terms are only for convenience of explanation and do not constitute any limitation on the present invention.

Claims

1. A method for preparing a core-shell bimetallic catalyst, characterized in that, The bimetallic catalyst comprises a core and a shell. The core comprises a molecular sieve as a support and bimetallic nanoparticles supported on the molecular sieve. The shell is a biochar shell covering the core. The bimetallic nanoparticles are composed of nano-sized Ni and a second metal M, wherein the second metal M is one of Mo, W, Co or Ti. The preparation method includes the following steps: (1) Add molecular sieve, nickel salt and second metal M salt to organic solvent and stir to form a uniform suspension A; (2) Add the biomass raw material to deionized water and stir to form a uniform suspension B; (3) Mix suspension A and suspension B, and stir under heating conditions of 80-100℃ until the liquid is completely evaporated to obtain a solid precursor mixture; (4) The solid precursor mixture obtained in step (3) is heated under an inert atmosphere and pyrolyzed and carbonized to reduce the nickel salt and the second metal salt. At the same time, the biomass raw material is carbonized to form a biochar shell coated on the bimetallic nanoparticles to obtain the catalyst primary product. After grinding, the catalyst is obtained. The molar ratio of the total metal ions of the biomass feedstock to the nickel salt and the second metal M salt is (0.5-2):

1.

2. The method for preparing the core-shell bimetallic catalyst according to claim 1, characterized in that, The molar ratio of Ni to the second metal M in the bimetallic nanoparticles is (1-5):

1.

3. The method for preparing the core-shell bimetallic catalyst according to claim 1, characterized in that, The size of the bimetallic nanoparticles is 5-10 nm; the molecular sieve is one of HZSM-5, HZSM-22, or SAPO-11.

4. The method for preparing the core-shell bimetallic catalyst according to claim 1, characterized in that, In step (1), the nickel salt is selected from one of nitrate, sulfate, acetate or hydrochloride; the second metal M salt is selected from one of ammonium M salt, nitrate, sulfate, acetate or hydrochloride.

5. The method for preparing the core-shell bimetallic catalyst according to claim 1, characterized in that, In step (1), the organic solvent is one of ethanol, propanol or tert-butanol.

6. The method for preparing the core-shell bimetallic catalyst according to claim 1, characterized in that, The biomass raw material is one of sucrose, D-glucose, D-sorbitol, citric acid, or cellulose pretreated with hydrogen peroxide.

7. The method for preparing the core-shell bimetallic catalyst according to claim 1, characterized in that, The heating rate for the pyrolysis carbonization is 5-15℃ / min, the temperature is raised to 500-800℃, and then calcined at a constant temperature of 500-800℃ for 1-4 hours.

8. The application of a catalyst prepared by the method of any one of claims 1-7 in the catalytic hydrodeoxygenation reaction of waste oil.

9. The application according to claim 8, characterized in that, The specific steps of the catalytic hydrogenation and deoxygenation reaction of waste oil are as follows: a core-shell bimetallic catalyst and waste oil raw material are added to a high-pressure reactor and reacted for 2-5 hours at a hydrogen pressure of 2-10 MPa and a reaction temperature of 250-450℃. The amount of the core-shell bimetallic catalyst is 5%-10% of the mass of the waste oil raw material.

Citation Information

Patent Citations

  • High-activity metallic nickel supported catalyst as well as preparation method and application thereof

    CN115739092A

  • Biological aviation kerosene catalyst with core-shell structure and application of biological aviation kerosene catalyst

    CN118002194A

  • Preparation method and application of nano nickel-based alloy catalyst

    CN119565628A

  • Carbon-coated nickel-palladium alloy nanoparticle composite material, preparation method therefor, and use thereof

    WO2024239574A1